Mental health literacy as a moderator: association between psychological vulnerability and adolescent anxiety - Qianying Hu; Yingyan Zhong; Jianhua Chen; Rumeng Chen; Enzhao Cong; Enzhao Cong; Yifeng Xu (Frontiers in Psychology)
BackgroundAdolescent anxiety’s underlying mechanisms remain unclear, which undermines adolescents’ social functioning. This study examined the moderating role of mental health literacy in the relationship between adolescent anxiety and psychological vulnerability.MethodsA cross-sectional study was conducted on 1,591 middle and high school students through online questionnaires in January 2023 in Guizhou Province, China. The Psychological Vulnerability Scale, Mental Health Literacy Scale, and Screen for Child Anxiety-Related Emotional Disorders were used to measure psychological vulnerability, mental health literacy, anxiety, and its five dimensions, including panic/somatic, generalized anxiety, separation anxiety, social phobia, and school phobia in adolescents, respectively.ResultsPsychological vulnerability was significantly correlated with adolescent anxiety and its dimensions (p < 0.05). The moderating role of mental health literacy on the relationship between psychological vulnerability and adolescent anxiety was left marginally significant (p = 0.07). Furthermore, mental health literacy significantly weakened the relationship between psychological vulnerability and social phobia (p < 0.05). The upward trend of anxiety as psychological vulnerability increases among the high mental health literacy group was significantly slower than the low mental health literacy group.ConclusionThose findings suggest educators should develop curriculum resources to strengthen the cultivation of mental health literacy among adolescents to promote adolescent mental health.